2008
DOI: 10.1111/j.1939-1676.2008.0181.x
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor CAG Repeat Polymorphisms in Canine Prostate Cancer

Abstract: Background: Relatively shorter lengths of the polymorphic polyglutamine repeat-1 of the androgen receptor (AR) have been associated with an increased risk of prostate cancer (PC) in humans. In the dog, there are 2 polymorphic CAG repeat (CAGr) regions.Objective: To investigate the relationship of CAGr length of the canine AR-gene and the development of PC. Animals: Thirty-two dogs with PC and 172 control dogs were used. Methods: DNA was extracted from blood. Both CAG repeats were amplified by polymerase chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 34 publications
(60 reference statements)
1
21
0
1
Order By: Relevance
“…An important difference between both species is that dogs show higher incidence of androgen independent tumors than humans (Bryan et al 2007). Neutered dogs have an increased risk of developing PC and they usually develop tumors from androgen independent cell (Lai et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…An important difference between both species is that dogs show higher incidence of androgen independent tumors than humans (Bryan et al 2007). Neutered dogs have an increased risk of developing PC and they usually develop tumors from androgen independent cell (Lai et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, most description are concerned with short alleles with polyglutamine tract glutamine residues on the receptor, which can do more high transactivation, depending on the inverse relationship with transcriptional activity (15). This potential relationship can be modified with the stage/degree at diagnosis (16) and the men who were diagnosed at more advanced ages seem to have longer CAG repeats (17), while 2 studies found no statistically significant relationship between short CAG length and formation of prostate cancer (18,19). Bratt et al (11) determined the relationship between CAG repeats and diagnosis at a young age, but did not find a relationship with high risk.…”
Section: Discussionmentioning
confidence: 95%
“…Das Prostatakarzinom entsteht aus den Basalzellen des Epithels der Ductuli [18,34]. Mögliche Ursachen sind in der Genetik und in der Immunhistologie zu suchen [22,23,32,33,34,51,52].…”
Section: Pathogeneseunclassified